Problems in preparation of legally binding documents for oncological and palliative patients and their solutions - P. G. Gabay; B. Sh. Kamolov (Опухоли головы и шеи)
Introduction. Oncological and palliative patients undergo treatment causing adverse events including mental and cognitive disorders leading to their inability to express their wishes in the legal sense. This affects the possibility of preparation of documents on disposal of property: wills, donation or sale and purchase agreements, letters of authorization.Aim. To consider problems arising when an oncological or palliative patient decides to dispose of their property and to suggest solutions to these problems.Materials and methods. An analysis of the current normative legal acts and legal precedents in the Russian Federation in the context of property disposal by severely ill patients was performed. Clinical guidelines on treatment of chronic pain in oncological and palliative patients, as well as Russian and international approaches to this therapy were considered.Results. Legal solutions for the considered problem appear to lack effectiveness. Use of tafalgin in treatment of severely ill patients can decrease risks and ease the process of preparation of documents on property disposal. This medication is indicated for chronic pain syndrome and unlike other pharmaceuticals is not an opioid analgesic and does not have severe side effects. Administration of tafalgin allows patients to retain mental clarity and avoid the risk of physical and psychological addiction.Conclusion. It is necessary to continue the search for new therapeutic approaches to chronic pain treatment taking into account needs and special aspects of oncological and palliative patients which would allow them to preserve full legal competency and dispose of their property without legal risks.